WHAT IS FELINE ACUPUNCTURE FOR? A FIRST APPROACH TO KNOWLEDGE OF FELINE PRACTITIONERS REGARDING VETERINARY ACUPUNCTURE IN BRAZIL - Scognamillo-Szabó, Márcia Valeria Rizzo; Paul, Erika Cristina (LUMEN ET VIRTUS, 2025)
Veterinary acupuncture is a complementary and alternative medicine practiced widely in Brazil and it is recognized as a specialty by the Federal Council of Veterinary Medicine. However, despite the growing interest of professionals for training and of clients for care, there are no studies on the knowledge of feline practitioners regarding veterinary acupuncture in Brazil. The present survey received 112 (complete) replies; the social media chosen for the distribution of the survey link were Instagram and WhatsApp. The majority of the respondents were feline veterinarians (80.35%) and from the southeastern region of Brazil (43.75%). Furthermore, 91% recommended acupuncture treatment to their patients while 8.93% didn’t nor were they able to identify which patients could benefit from acupuncture. When asked to which of the conditions displayed, they would recommend the technique, neuromusculoskeletal were, by far, the most common diseases for referral to acupuncture. Our results, despite the small sample, point to the fact that acupuncture is still unknown to most veterinarians, and it is therefore rarely indicated. Also, there is a lack of scientific data in Brazil that could elucidate and enrich statistics on acupuncture, furthermore, most Brazilian veterinarians do not respond to surveys because they don’t know the importance of it.